Cloud technologies in teaching modeling of complex systems - R. Iu. Lopatkin; V. A. Ivashchenko (Academy of Cognitive and Natural Sciences, 2013)
Purposeful and systematic teaching of the method of modeling brings students closer to the methods of scientific knowledge, ensures their intellectual development. But for this purpose it is necessary to have at one's disposal a whole range of means and tools, which will allow to pass a way from creating a model to checking its consistency and adequacy. If we speak about sufficiently complex objects of research, computing resources required for calculation can significantly exceed the capabilities of a student's personal computer and the modeling process itself can take an indefinite amount of time. Just in this case the cloud systems come to the rescue, which can provide the necessary resources to calculate the model.